2011
DOI: 10.1021/bc2001352
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Morphine–Glucose-6-phosphate Dehydrogenase Conjugates by Mass Spectrometry

Abstract: A key characteristic of the analyte-reporter enzyme conjugate used in the enzyme-multiplied immunoassay technique (EMIT) is the inhibition of the conjugate enzyme upon anti-analyte antibody binding. Toward understanding the antibody-induced inhibition mechanism, characterization of morphine-glucose-6-phosphate dehydrogenase (G6PDH) conjugates as model EMIT analyte-reporter enzyme conjugates was pursued. Morphine-G6PDH conjugates were prepared by acylating predominantly the primary amines on G6PDH with morphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Since the modification reaction was random and undirectional, a high conjugation degree was necessary to ensure the activity repression even though the activity of CG-G6PD conjugates might be cut down. This result agreed to the previous study [15].…”
Section: Effects Of Cg On the Residual Activity Of Cg-g6pd And The Repression Of G6pd Activity (Cg-g6pd Conjugates Were Prepared In Pbs Bsupporting
confidence: 94%
See 3 more Smart Citations
“…Since the modification reaction was random and undirectional, a high conjugation degree was necessary to ensure the activity repression even though the activity of CG-G6PD conjugates might be cut down. This result agreed to the previous study [15].…”
Section: Effects Of Cg On the Residual Activity Of Cg-g6pd And The Repression Of G6pd Activity (Cg-g6pd Conjugates Were Prepared In Pbs Bsupporting
confidence: 94%
“…These results indicated that G6PD was successfully labeled with CG, and the degree of conjugation increased with CG. Recently, another work also suggested the dependence of conjugation degree on CG amount [15]. In Fig.…”
Section: Identification Of the Conjugates 311 Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresismentioning
confidence: 90%
See 2 more Smart Citations
“…A similar strategy working backward to deduce amino acid sequence containing the conjugation site has been adopted in other studies as well. 30 (3) Optionally, refine the MASCOT searching criteria to expand the variable modification of the pharmacophore-linker to additional residues identified from step 2. The final parameter setting can be generalized to perform a straightforward MASCOT search on similar conjugates.…”
Section: ■ Resultsmentioning
confidence: 99%